Karakteristik Fisiko-Kimia dan Sensori Kerupuk Pangsit dengan Kombinasi Tepung Ikan Motan (Thynnichthys thynnoides) - Riyan Saputra; Indah Widiastuti; Rodiana Nopianti (Jurnal FishtecH, 2016)
The purpose of the research was to know physicochemical and sensory characteristic of dumplings with combination of carp fish meal. The research was conducted on February until March 2016. The research method was used randomized block design (RBD). The treatments were 0%, 2.5%, 5%, 7.5%, 10%, and 12.5% of fish meal. The parameters of this reseach were chemical analysis such as water content, ash content, protein content, lipid content, carbohydrate content, and calcium; physical analysis were elasticity; colour and sensoric analysis (colour, taste and texture). The results showed that treatment gave significant effect on water content, ash content, protein content, carbohydrate content, and calcium; chroma, hue and sensoric analysis (colour, taste, and texture), but there were no effect on lipid content, and lightness. The water content 1.09%-2.86%, ash 1.66%-8.48%, protein 5.92%-12.79%, charbohidrat 41.14%-63.26%, calcium 35.88%-50.90%. The croma of this dumplings crackers were 10.40-24.20%, hue 55.30%-73.70%, texture 501.5-826.7. Colour sensory analysis of dumplings crackers were 2.18-4.18, taste 2.20-4.16, texture 2.62-4.28. The best treatment was A2 (5% combination carp fish meal).